Is the discovery of the novel human betacoronavirus 2c EMC/2012 (HCoV-EMC) the beginning of another SARS-like pandemic? - Chan, Jasper F.W. (J Infect, 2012)
Fouchier et al. reported the isolation and genome sequencing of a novel coronavirus tentatively named “human betacoronavirus 2c EMC/2012 (HCoV-EMC)” from a Saudi patient presenting with pneumonia and renal failure in June 2012. Genome sequencing showed that this virus belongs to the group C species of the genus betacoronavirus and phylogenetically related to the bat coronaviruses HKU4 and HKU5 previously found in lesser bamboo bat and Japanese Pipistrelle bat of Hong Kong respectively. Another patient from Qatar with similar clinical presentation and positive RT-PCR test was reported in September 2012. We compare and contrast the clinical presentation, laboratory diagnosis and management of infection due to this novel coronavirus and that of SARS coronavirus despite the paucity of published information on the former. Since 70% of all emerging infectious pathogens came from animals, the emergence of this novel virus may represent another instance of interspecies jumping of betacoronavirus from animals to human similar to the group A coronavirus OC43 possibly from a bovine source in the 1890s and the group B SARS coronavirus in 2003 from bat to civet and human. Despite the apparently low transmissibility of the virus at this stage, research preparedness against another SARS-like pandemic is an important precautionary strategy.